The FLUKA Code: An Accurate Simulation Tool for Particle Therapy - Battistoni, Giuseppe; Bauer, Julia; Boehlen, Till T.; Cerutti, Francesco; Chin, Mary P. W.; Dos Santos Augusto, Ricardo; Ferrari, Alfredo; Ortega, Pablo G.; Kozłowska, Wioletta; Magro, Giuseppe; Mairani, Andrea; Parodi, Katia; et al. (Frontiers in Oncology, 2016)
onte Carlo (MC) codes are increasingly spreading in the hadrontherapy community due to their detailed description of radiation transport and interaction with matter. The suitability of a MC code for application to hadrontherapy demands accurate and reliable physical models capable of handling all components of the expected radiation field. This becomes extremely important for correctly performing not only physical but also biologically-based dose calculations, especially in cases where ions heavier than protons are involved. In addition, accurate prediction of emerging secondary radiation is of utmost importance in innovative areas of research aiming at in-vivo treatment verification. This contribution will address the recent developments of the FLUKA MC code and its practical applications in this field. Refinements of the FLUKA nuclear models in the therapeutic energy interval lead to an improved description of the mixed radiation field as shown in the presented benchmarks against experimental data with both 4 He and 12 C ion beams. Accurate description of ionization energy losses and of particle scattering and interactions lead to the excellent agreement of calculated depth-dose profiles with those measured at leading European hadron therapy centers, both with proton and ion beams. In order to support the application of FLUKA in hospital based environments, Flair, the FLUKA graphical interface, has been enhanced with the capability of translating CT DICOM images into voxel-based computational phantoms in a fast and well-structured way. The interface is capable of importing also radiotherapy treatment data described in DICOM RT standard.In addition the interface is equipped with an intuitive PET scanner geometry generator and automatic recording of coincidence events. Clinically similar cases will be presented both in terms of absorbed dose and biological dose calculations describing the various available features.